Rastreadores para eventos adversos a medicamentos na saúde mental infantil - Santos, Sandna Larissa Freitas dos (2021)
The use of tracking tools to identify adverse drug events has promoted improved care and the measurement of preventable damage. However, there is a lack of data in the context of child mental health, mainly focused on community services. The objectives of this dissertation were: to carry out an integrative review of the tracers used to identify adverse drug events in children, as well as to describe the tracers by the global trigger tool tool, among the adverse events in children who use psychotropic drugs monitored in two Centers of Children and Youth Psychosocial Care in Fortaleza-Ceará. The integrative review was carried out with eight studies showing that the most cited tracers were: abrupt cessation of medication use, hospital readmission within thirty days with and transfer to a higher level of care. The descriptive study was carried out with 112 medical records of children who started care from January to December 2017 in the services. Data were collected from October 2019 to November 2020 using a form divided into four parts: identification of the child, use of medications, detection of adverse events and presence of trackers. The data were stored in the Epi Info version 3.5.2 program and analyzed in the Statistics and Data Science program, version 12. For the analysis of the results, simple descriptive statistics of the variables were performed, using relative and absolute frequency, mean and deviation -standard. It was found that 57.2% were aged between 9 and 12 years old, 67.8% attended school and 68.2% had psychological development disorders. The average of medication per child was 1.71 and among the most prescribed were 100% risperidone, followed by valproic acid and 16% periciazine each. A total of 42 adverse drug events were found in 36 medical records, with agitation 29.7% and aggressiveness 16.2% being the most prevalent. A total of 50 tracers were detected in 83.3% of the records that identified events, the most common were: combination of psychotropic medications 32%, abrupt reduction of medication dose 22% and abrupt cessation of medication 12%. It was demonstrated that the global trigger tool evidenced psychotropic adverse events through the detection of tracers in children and that there is a need to offer interventions to improve the quality of psychiatric therapy within community services.